2005
DOI: 10.1016/j.nimb.2004.12.111
|View full text |Cite
|
Sign up to set email alerts
|

Studies of nanotube channeling for efficient beam scraping at accelerators

Abstract: While particle beam steering (and in particular, "scraping") in accelerators by bent channeling crystals is an established technique extensively tested at IHEP Protvino and other major high-energy labs, an interesting question is how one could improve channeling capabilities by applying modern nanotechnology. Theoretical research of nanotube channeling was in progress over recent years. In this work, we assess potential benefits from nanotube channeling for real accelerator systems. We report simulation studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The crystal size is 4 × 2 × 0.3 mm 3 . Strong crystalline fields allow one to bring the period λ u of bending down to the hundred or even ten micron range, which is two to five orders of magnitude smaller than the period of a conventional undulator [65][66][67][68]. Right bottom a Si 1−x Ge x superlattice crystalline undulator with four periods.…”
Section: Why a Crystalline Undulator?mentioning
confidence: 99%
“…The crystal size is 4 × 2 × 0.3 mm 3 . Strong crystalline fields allow one to bring the period λ u of bending down to the hundred or even ten micron range, which is two to five orders of magnitude smaller than the period of a conventional undulator [65][66][67][68]. Right bottom a Si 1−x Ge x superlattice crystalline undulator with four periods.…”
Section: Why a Crystalline Undulator?mentioning
confidence: 99%
“…Besides such diagnostic applications, we would like to mention the possibility of producing nanosized ion beams with the nanotubes embedded in various dielectric media for applications in biomedical research [6,12,13]. Our findings can shed more light on the issue of shape of the spatial distribution of channeled ions suitable for such applications, especially if there are concerns about the increase of the proton flux in the peripheral region of a nanosized ion beam at the expense of the flux in its central region.…”
Section: Discussionmentioning
confidence: 83%
“…Theoretical modeling of ion channeling through carbon nanotubes has reached a mature level [1][2][3] whereas experimental realization of this process is still at the preliminary stage [4,5]. Nevertheless, theoreticians continue to explore possible applications of ion channeling through the nanotubes, beginning with those based on the angular distributions of channeled ions, e.g., for the purpose of deflecting ion beams in accelerators [6,7] or determining some structural details of the short nanotubes using the rainbow effect [8][9][10][11]. Besides, theoretical studies of the spatial distributions of channeled ions have demonstrated the possibility of creating nanosized ion beams, which could find interesting applications in biomedical research and for materials modification [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations